2009
DOI: 10.1152/ajpheart.00358.2009
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate is an important endogenous cardioprotectant released by ischemic pre- and postconditioning

Abstract: Exogenous sphingosine 1-phosphate (S1P) is an effective cardioprotectant against ischemic injury. We have investigated the hypothesis that S1P is also an important endogenous cardioprotectant released during both ischemic preconditioning (IPC) and ischemic postconditioning (IPOST). IPC of ex vivo rat hearts was instituted by two cycles of 3 min ischemia-5 min reperfusion prior to 40 min of index ischemia and then 40 min of reperfusion. IPC resulted in 70% recovery of left ventricular developed pressure (LVDP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 29 publications
6
81
0
Order By: Relevance
“…When present during pre-or postconditioning, the mixed S1P1/S1P3 receptor antagonist VPC23019 blocked protection afforded by either 2 cycles of preconditioning or 4 postindex ischemia cycles. 13 This antagonist also blocked preconditioning of isolated rat cardiac myocytes subjected to hypoxia-reoxygenation injury. The study also showed increased release of S1P from myocytes in response to preconditioning, suggesting that S1P released in response to preconditioning protects the heart by binding to membrane S1P receptors.…”
Section: Blood S1p and Association With Lipoproteinsmentioning
confidence: 96%
See 1 more Smart Citation
“…When present during pre-or postconditioning, the mixed S1P1/S1P3 receptor antagonist VPC23019 blocked protection afforded by either 2 cycles of preconditioning or 4 postindex ischemia cycles. 13 This antagonist also blocked preconditioning of isolated rat cardiac myocytes subjected to hypoxia-reoxygenation injury. The study also showed increased release of S1P from myocytes in response to preconditioning, suggesting that S1P released in response to preconditioning protects the heart by binding to membrane S1P receptors.…”
Section: Blood S1p and Association With Lipoproteinsmentioning
confidence: 96%
“…11 These enzymes seem to be an important source of endogenous S1P in the heart, and their appearance in mice as early as E8.5 suggests a key role in cardiac development. 12 S1P generation in the heart is upregulated in response to a transient ischemia, suggesting a beneficial contribution of the SPK-S1P axis to ischemic pre-and postconditioning 13 (…”
mentioning
confidence: 99%
“…suggesting the contribution of the SphK-S1P axis to ischemic preconditioning and ischemic post-conditioning [26]. Mice heterozygous for deletion of the S1P-degradating enzyme S1P lyase gene and wild-type mice receiving an SPL inhibitor, which showed elevated S1P levels in both plasma and cardiac tissues, had reduced sensitivity to ischemia/reperfusion injury, raising a possibility of cardioprotection with an S1P lyase inhibitor in clinical settings [27].…”
Section: Cardiac Fibrosismentioning
confidence: 99%
“…Infarct size in SphK1-null mice appeared to be increased and the hearts of these mice demonstrated a poor response to ischemic preconditioning or postconditioning stimulus [54]. VPC23019 blocked cardioprotection in ex vivo rat hearts and in isolated cardiomyocytes [55].…”
Section: Hypoxic Conditions and Cytoprotectionmentioning
confidence: 99%